Strategic Management of Nature-Based Tourism in Ijen Crater in the Context of Sustainable Tourism Development - Putri, Sandra Dhesitta; Soemarno, Soemarno; Hakim, Luchman (Journal of Indonesian Tourism and Development Studies, 2015)
The aim of the study is to define the strategic management of nature based tourism in Ijen crater, East Java. From the perspectives of accessibility, problems facing by accessibility are related to the travel distance and forest road quality. Ijen craters have three important aspect in competitiveness tourism aspect, namely something to see (mountain landscape), something to do (trekking, hiking, bird watching), and something to buy (meals). The future development of such attraction should be meets ecotourism principles. This study found that improving tourism facility and infrastructure were important aspects. The development and improvement of tourism facility and infrastructure, however, should be incorporates ecotourism principles. In such a case, the conservation, local people and community development becomes crucial issue. Involvement of stakeholder and local community in facility and infrastructure will increase the quality and sustainability of infrastructure and tourism facility. Keywords: ecotourism strategy, tourism management.